2020
DOI: 10.3390/ma13122689
|View full text |Cite
|
Sign up to set email alerts
|

Wear Morphology on the Surfaces of CoCrMo Unicompartmental Knee Joint Endoprostheses as Elements of Metal–Metal Friction Nodes

Abstract: The article assesses the strength and structural parameters of load-bearing layers of metal biobearings made of CoCrMo alloy. The research material consisted of unicompartmental knee joint endoprostheses used in the human body, removed due to excessive wear. No patient participated in the examinations. The endoprostheses used as research material underwent the liquidation procedures in the hospital, which has all necessary permissions and certifications to perform endoprosthetic procedures. Endoprostheses sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The highest number was observed for hip joint replacement surgeries performed in 2005-2019, although with a steadily decreasing trend, amounting for 85.9% of all joint replacement surgeries in 2005, and 63.1% in 2019, which translated into a decrease of 22.8%. However, throughout the study, the escalation of knee joint replacement surgeries was observed as their percentage increased from 13.4% in 2005 to 35.3% in 2019, as shown in Figure 3 [19][20][21][22][23][24][25][26][27]. In 2019, 54,490 primary hip arthroplasty (91.88%) and 4816 (8.12%) revision arthroplasty procedures were performed (including 564 revision operations without replacing components).…”
Section: Statistical Evaluation Of the Number Of Surgeries And Costs Of Hip-joint Replacement In Polandmentioning
confidence: 90%
See 1 more Smart Citation
“…The highest number was observed for hip joint replacement surgeries performed in 2005-2019, although with a steadily decreasing trend, amounting for 85.9% of all joint replacement surgeries in 2005, and 63.1% in 2019, which translated into a decrease of 22.8%. However, throughout the study, the escalation of knee joint replacement surgeries was observed as their percentage increased from 13.4% in 2005 to 35.3% in 2019, as shown in Figure 3 [19][20][21][22][23][24][25][26][27]. In 2019, 54,490 primary hip arthroplasty (91.88%) and 4816 (8.12%) revision arthroplasty procedures were performed (including 564 revision operations without replacing components).…”
Section: Statistical Evaluation Of the Number Of Surgeries And Costs Of Hip-joint Replacement In Polandmentioning
confidence: 90%
“…A detailed summary in this regard is illustrated in Figure 1 below. The escalation of performed arthroplasty procedures has also been observed in recent years in Poland [19]. In 2019, a total of 94,000 were carried out (5821 more compared to the previous year, which was 88,179).…”
Section: Statistical Evaluation Of the Number Of Surgeries And Costs Of Hip-joint Replacement In Polandmentioning
confidence: 92%
“…Further on, FEA was performed only in static position (standing on one leg) and not also at common activities of daily living when much larger forces appear. Szarek et al have clearly shown that during level walking and going downstairs, the knee joint force reaches 283% and 410% of body weight, respectively [ 37 ]. Finally, bone ingrowth measurements were not studied in concordance with previously described methods [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of this research focuses on biocompatibility and mechanical properties and there is little research on its antibacterial and antibiofilm modification. [18][19][20] With the rapid development of nanoscience and nanotechnology, various antibacterial nanomaterials, such as metal nanoparticles, 21 carbon nanotubes, 22 graphene and their derivatives 23,24 have been widely studied. Graphene oxide (GO) is a type of graphene with abundant oxygen bonds at the edges and defect sites, such as carboxyl groups (-COOH), carbonyl groups (-C=O), and hydroxyl groups (OH) on the access side.…”
Section: Introductionmentioning
confidence: 99%